2011
DOI: 10.1074/jbc.m111.265900
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-receptor Interaction between Triterpenoids and the 11β-Hydroxysteroid dehydrogenase type 2 (11βHSD2) Enzyme Predicts Their Toxic Effects against Tumorigenic r/m HM-SFME-1 Cells

Abstract: The present study deals with in silico prediction and in vitro evaluation of the selective cytotoxic effects of triterpenoids on tumorigenic human c-Ha-ras and mouse c-myc cotransfected highly metastatic serum-free mouse embryo-1 (r/m HM-SFME-1) cells. Ligand fitting of five different triterpenoids to 11␤-hydroxysteroid dehydrogenase type 2 (11␤HSD2) was analyzed with a molecular modeling method, and glycyrrhetinic acid (GA) was the best-fitted triterpenoid to the ligand binding site in 11␤HSD2. Analysis of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…We recently found that GA demonstrated significant growth inhibitory activity toward a CNS tumor cell line [13], suggesting that GA can be utilized for the antitumor drug development. However, whether or not GA can bind to the HMGB1-DNA complex is not known.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently found that GA demonstrated significant growth inhibitory activity toward a CNS tumor cell line [13], suggesting that GA can be utilized for the antitumor drug development. However, whether or not GA can bind to the HMGB1-DNA complex is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling of the 3D structure of the HMGB1-DNA complex was executed as previously reported [13]. In brief, the HMGB1 (NCBI reference sequence: NP_002119.1) and the duplex sequences and their crystal structure coordinates were loaded into the MOE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study revealed that GSH could be an important factor for the selective toxicity toward central nervous system-derived tumor cells [20], which suggests that targeting the key enzyme for GSH homeostasis, namely GCL, with highly selective inhibitors could be utilized for controlling the development and progression of cancer. GCL is a heterodimeric enzyme with a 73-kDa catalytic subunit and a 31-kDa modifier subunit, and GCLC contains the glutamate, cysteine and ATP binding sites and has catalytic activity even as a monomer [1,21].…”
Section: Introductionmentioning
confidence: 99%